A case study of practical coach assessment - Chia, Yong Bin (2016)
The primary purpose of this study was to explore the use of a coach assessment instrument called World Rugby Coaching Profile Proforma as a generic tool to be used by coaches from various sports with the aim of assessing their coaching effectiveness. A total of 15 participants (coaches) representing a variety of sports (i.e. badminton, soccer and rugby) took part in this research to perform self-assessments using the instrument before and after conducting their coaching sessions. The data collected were analysed using reflective practitioner theory as the study’s theoretical framework. Results indicated that majority of the participants perceived their coaching effectiveness to be higher after coaching with perceived rankings of their effectiveness in their coaching domains in the following order: Delivery (Rank 1), Delivery Interaction (Rank 2), Planning (Rank 3), Planning Operation (Rank 4) and Game Knowledge (Rank 5). Finally, there were significant differences in planning operation and delivery interaction (p<0.05). The findings are discussed in terms of their implications for coaching effectiveness.